Optimization of welding in shipbuilding in peru - Gamarra Chinchay, Hugo Eliseo (2011)
The present work studies the productivity of the weld in naval construction, starting off of an analysis of the production in our means happening to present some techniques or alternatives to increase the productivity of the weld in naval construction. We will begin describing some basic knowledge of weld, productivity and like determining the productivity of weld in the naval construction, in addition to because of the analysis of the productivity of the weld in our means. Also some factors are exposed that are going to influence in the production of the weld, as they are the yield by fusion, the selection of the materials, the type of steel, the type of procedure, etc. On the other hand, the statistical data taken in the zone from work appear that will serve to measure the productivity of the weld based on the kilograms of deposited metal and the yield by fusion of several types of electrodes. Finally, the proposal appears to increase the productivity of the weld in our means on the basis of the observed problems and the made calculations, presenting in addition two welding procedures that can be applied in our means, and a method that will facilitate the solution of the problems that are detected in the shipyard.